Analysis of the Need for Differential Calculus Teaching Modules to Improve the Learning Independence of Students in the Mathematics Education Study Program, Faculty of Mathematics and Natural Sciences, UNM Makassar - Rusli; Abdul Rahman; Andika Saputra; Musa, Hastuty (PT ARRUS Intelektual Indonesia, 2025)
This study aims to analyze the needs for a Differential Calculus teaching module that supports independent learning among students in the Mathematics Education Study Program at FMIPA UNM Makassar. In the context of the Fourth Industrial Revolution, independent learning is essential for developing creative thinking, problem-solving skills, and adaptability to technological change. Using a descriptive qualitative approach, this study collected data through diagnostic tests, classroom observations, questionnaires, interviews, and document analysis of existing teaching materials. The findings reveal that students expect a teaching module that not only presents theoretical content but also includes real-life applications, visual simulations, and contextual examples to facilitate understanding of abstract mathematical concepts such as derivatives. Students also prefer materials that use simple and structured language, step-by-step examples, topic summaries, and practice questions with immediate feedback. Furthermore, students highly value digital and interactive formats that can be accessed via mobile devices, supporting flexible and autonomous learning. This study highlights the importance of developing need-based teaching modules that are student-centered, visually engaging, and technologically integrated. Such modules are expected to enhance independent learning, improve student motivation, and deepen conceptual understanding of differential calculus. The results also provide a foundation for designing similar learning resources for other abstract and complex courses in mathematics education.